Green Synthesis of [EMIm]Ac Ionic Liquid for Plasticizing MC-based Biopolymer Electrolyte Membranes - Sun Theo Constan Lotebulo Ndruru; Deana Wahyuningrum; Bunbun Bundjali; I Made Arcana (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Lithium-ion batteries (LIBs) are favorable power source devices at the last two decades, owing to high energy density, rechargeable, long life cycle, portable, safe, rechargeable, good performance and friendly environment. To support their development, in this research has been successfully prepared polymer electrolyte membrane, a main component of LIBs, based on 1-ethyl-3-methylimidazolium acetate ([EMIm]Ac) ionic liquid-plasticized methyl cellulose/lithium perchlorate (MC/LiClO4). [EMIm]Ac ionic  liquid was easy synthesized by metathesis reaction between 1-ethyl-3-methylimidazolium bromide ([EMIm]Br) ionic liquid and potassium acetate (CH3COOK) at ambient temperature, for 1 hour. [EMIm]Ac ionic liquid was functional groups analyzed with Fourier Transform Infra-red (FT-IR) and structural analyzed with 1H-Nuclear Magnetic Resonance (NMR) and 13C-NMR. [EMIm]Ac ionic liquid-plasticized MC/LiClO4 biopolymer electrolyte membrane was prepared by casting solution, with [EMIm]Ac ionic liquid content, 0, 5, 10, 15, 20, 25, and 30% (w/w). Effect of 15% (w/w) [EMIm]Ac ionic liquid incorporation to MC/LiClO4 showed the best condition and selected as the optimum condition with conductivity, tensile strength, elongation break, and thermal stability of 9.160×10-3 S.cm-1, 24.19 MPa, 36.43%, ~256 and ~370 ºC, respectively. These results confirm that [EMIm]Ac ionic liquid can plasticize biopolymer electrolyte membranes of MC/LiClO4 to be appealing performances to fulfill the LIB’s separator requirement. Copyright © 2019 BCREC Group. All rights reserved